PENYELESAIAN TINDAK PIDANA PENCURIAN IKAN DI LUBUAK LARANGAN MENURUT HUKUM ADAT DI NAGARI PULASAN KEC.TANJUNG GADANG KAB.SIJUNJUNG - Devan Saddana Putra, Nurlinda Yenti , (Fakultas Hukum Universitas Tamansiswa Padang, 2022)
The crime of fish theft in Lubuk Prohibition according to custom in Nagari Pulasan, Tanjung Gadang District, Sijunjung Regency. Customary law dispute resolution also has a mechanism that is seen as customary procedural law. There are stages in the customary dispute settlement mechanism, starting with reports or complaints from the parties or being caught red-handed/caught red-handed, either by members of the public or other authorities, up to the implementation of the decision. Based on the results of the research and discussion, it can be concluded as follows: the settlement of the crime of fishing theft in Lubuk Larangan in Nagari Pulasan, Tanjung Gadang District, Sijunjung Regency, the settlement includes: Complaints, summons, place of settlement process, preparatory meetings, decisions of deliberation sessions, implementation of decision making, sanctions in adat. Obstacles encountered in solving the perpetrators of illegal fishing in Lubuak Larangan in Nagari Pulasan, Tanjung Gadang District, Sijunjung Regency include: First, low individual understanding of customs with a lack of individual understanding of customs. The two Nagari Pulasan communities prefer to resolve this through the police rather than through customary law. Because the process of solving fish theft in Lubuak is prohibited according to adat in Nagari Pulasan, the process is a bit slow.